GREEN FINANCE IN ECONOMIC RESEARCH: A BIBLIOMETRIC ANALYSIS - Andrea Čandová; Jan Pokorný (Trendy v podnikání)
Green finance is a financial system that supports sustainable development and environmental protection. It involves financial instruments and policies designed to fund environmentally friendly projects and reduce carbon emissions. International organizations such as the UN, EU, and World Bank are driving the adoption of green finance by setting standards, providing funding, and encouraging sustainable investments. These organizations are promoting a shift toward a low-carbon economy by supporting green projects, incentivizing sustainable practices, and mobilizing public and private finance for environmental initiatives. This paper aims to assess current economic research on green finance, focusing on bibliometric and thematic analysis. Two research samples are defined: a global sample and an EU sample, based on output data from the Web of Science publication database. The analysis confirms the novelty of the topic, with a primary focus on CO2 emission reduction, green bonds, sustainable development, and innovation. When comparing countries, China emerges as a leading research hub, while within the EU, France, Germany, and Italy are the main contributors. However, European research is also influenced by collaboration, particularly with China. The limitations of this research are rooted in the reliance on the Web of Science database. Further research could delve deeper into specific thematic areas, such as the utilization of green bonds in both European and non-European contexts, or exploring the application of Pigouvian taxes to address emissions.